Adapting to online education: insights from computer science teachers - Monika Mladenović (Springer, 2023)
Abstract This paper explored the attitudes and roles of computer science (CS) teachers in elementary and high schools in Croatia in the period from completely online to "normal" schooling. The research was conducted in two phases to gain insight into the adaption of online education in schools. The first part of the research was a quantitative study conducted during online education in 2019/2020 among 538 elementary and high school informatics teachers across Croatia. Data were collected from an online survey. The second part of the research was a qualitative study conducted in 2022, employing interviews for data collection. The interview questions were designed based on the survey results mentioned above. The results showed that CS teachers had a significant role in implementing online schools, acting as implementers of tools for online teaching and as helpdesk IT support to other teachers. Still, formal education nowadays is affected by online schooling, and some online practices are now adopted into regular teaching. Therefore, the findings can serve as a guideline for future education related to the digital competencies of teachers and students.